An innovative community care approach for pregnant women and children in malaria endemic remote areas in Cambodia - (:unkn) unknown (My University, 2013)
Malaria is still prevailing in most Southeast Asian Regions, even if morbidity and mortality rates are much less than in Africa. In order to reduce health access inequalities and spatial discrepancies where no health structures are to be found, some countries like Cambodia (followed by Lao PDR and the Philippines) have initiated singular interventions in far-off areas, based on community based interventions. In this presentation, I will take the case study of Cambodia with its Village Malaria Worker Project
Keywords: African Research